Respuesta :
Answer:
k=6
Step-by-step explanation:
The parabola that opens up and passes through (-3,-3) will have equation,
[tex]f(x) = {x}^{2} - 12[/tex]
The parabola the opens up a d passes through (-3,3) will have equation:
[tex]g(x) = {x}^{2} - 6[/tex]
We want to determine the value of k, for which,
[tex]g(x) = f(x) + k[/tex]
We rewrite g(x) in terms of f(x) to get:
[tex] {x}^{2} - 6 = {x}^{2} - 12 + 6[/tex]
[tex]g(x) \to({x}^{2} - 6 )= f(x) \to ({x}^{2} - 12 )+k \to6[/tex]
Therefore;
[tex]g(x) = f(x) + 6[/tex]
Hence k=6
Answer:
It's B.
Step-by-step explanation:
When two equations are the same, but in different section of the graph; like this one, count the columns until you get to the other curve. And that's the "K" for the equation.